(untitled) (Jurnal Arsitektur ARCADE, 2026)
The rapidly evolving retail industry demands a deep understanding of environmental stimuli that can regulate visitors’ emotional states. Although lighting has been shown to be a crucial interior element of store ambiance, its impact on human psychophysiology, which shapes consumer behavior, still requires further exploration. This article aims to analyze the literature on how lighting influences visitors’ emotional states, using Heart Rate Variability as an objective psychophysiological indicator. This review was conducted following PRISMA guidelines by searching through academic databases from 2015 to 2025. The data synthesis results indicate a strong correlation between lighting parameters, such as color temperature and illumination, and the autonomic nervous system. The findings highlight that certain lighting manipulations significantly affect fluctuations in HRV metrics, which reflect visitors’ arousal and cognitive load. This internal state implicitly mediates the formation of positive emotions that ultimately influence purchase intentions. This review provides a data-driven framework for interior designers and retail owners to implement lighting strategies to optimize visitors’ emotional experiences. Furthermore, this article identifies gaps in neuromarketing research and provides directions for future research on the use of neuroscience technology in retail marketing.